Evaluation Of Vehicle Loading On Board KMP. Kerapu On The Rasau Jaya - Teluk Batang Track, West Kalimantan Province - Surnata Surnata; Siti Nurlaili Triwahyuni; Wahyu Dwi Putri Sang Fajar (IWTJ : International Water Transport Journal, 2022)
Rasau Jaya Port is a port located in Kubu Raya Regency, in West Kalimantan Province which has an important trajectory, namely Rasau Jaya -Teluk Batang which can be navigable by KMP. Kerapu. This line connects Kubu Raya Regency with North Kayong Regency. This port is an inland port which is the most important transportation access place in West Kalimantan. In the transportation system, security and safety are the top priorities as a form of providing good services for service users. Safety is shown not only to service users and ship operators, but also to vehicles transported on board. As is the handling of vehicle loading on board. The better the handling of cargo on board, the better the level of security and safety of the vehicle on board. The level of conformity of vehicle loading on ships has been regulated in Government Regulation Number 62 of 2019 concerning minimum service standards for crossing transportation, this study was conducted to determine the level of conformity of vehicle loadingand find out the load capacity based on SUP with current conditions. Efforts that need to be improved are the supervision of the loading of vehicles on board ships, port operators are required to weigh and measure cargo to carry out safe loading, and socialization is held to service providers with minimal services on board ships on safe, safe and comfortable loading of vehicles.